EFEKTIFITAS TEKNIK RILAKSASI DALAM MENGURANGI WAKTU PERILAKU HIPERAKTIF ANAK TUNAGRAHITA RINGAN DI SDLB N 20 PONDOK II PARIAMAN - Arie Putri Lejarnani, Asep Ahmad Sopandi, Ganda Sumekar (Universitas Negeri Padang, 2013)
The research was motivated by the problems that appear in the field in SDLB N 20 Pondok II Pariaman, of a child class IV SDLB N behavior of hyperactive children have turned out. This research Single Subject Research approach, with desain A-B-A. Results of this study indicate that theto effective technique decrease hyperactive behavior in children mild mental retardation fourth grade II cottage SDLB N 20 Pariaman.